Upaya Pengendalian Persediaan Bahan Baku pada Pabrik Tahu NTB Menggunakan Metode Material Requirement Planning - Thamrin, Revi Reskya; Helma, Helma (UNIVERSITAS NEGERI PADANG, 2023)
Getting maximum profit is the main goal of every company. To achieve this goal, it is important for companies to control raw material inventories. The NTB Tofu Factory is a factory engaged in food production. The number of requests at the NTB Factory is uncertain which can make the amount of supply exceed or less than demand. So that research will be carried out to control the supply of raw materials and find out the total inventory cost using the Material Requirement Planning method. The lot sizing used are the Lot for Lot technique and the Economic Order Quantity. This research is applied research. This study obtained the results that the most effective technique to apply is the lot for Lot technique because it has the minimum cost. For soybean, a total inventory cost of ???????? 1.200.000 is obtained which can save costs of 66,7%. As for flour raw materials, the total inventory cost value was ???????? 360.000 which could save costs of 59,3%.